Analisa Perbandingan Model Pembelajaran Project-Based Learning berbantuan Software Simurelay terhadap Hasil Belajar Siswa - Rahayu, Indah Dwi; Aswardi, Aswardi (Jurnal Pendidikan Teknik Elektro, 2024)
This research was conducted to determine whether there are significant differences in student learning outcomes using the Project-Based Learning model with and without simurelay software in the class XI Electric Motor Installation subject at SMKN 1 Bukittinggi. In the learning process for Electric Motor Installation at SMKN 1 Bukittinggi, the use of the Project-Based Learning model has not been implemented properly and still uses the lecture method, so learning focuses on educators which causes students to be less active and can reduce student learning outcomes. The Project-Based Learning model assisted by simurelay software increases student activity so that student learning outcomes increase and learning objectives are achieved. The type of research used is comparative research with a non-equivalent control group design. The subjects in this research were class XI students at SMKN 1 Bukittinggi in the 2023/2024 academic year. The instruments used in this research are pre-test and post-test (performance test). The research results obtained are that there is a significant difference in learning outcomes between learning using the Project-Based Learning model assisted by simurelay software and learning without simurelay software.